Towards Size‐Controlled Deposition of Palladium Nanoparticles from Polyoxometalate Precursors: An Electrochemical Scanning Tunneling Microscopy Study. Issue 7 (24th February 2021) - Bock, Nicolas; De Clercq, Astrid; Seidl, Lukas; Kratky, Tim; Ma, Tian; Günther, Sebastian; Kortz, Ulrich; Heiz, Ueli; Esch, Friedrich
Abstract: We present a novel in situ electrochemical approach to deposit small size‐controlled palladium(0) clusters from 12‐Pd II ‐oxo‐metalate precursors. These clusters are formed through the reductive surface polarization of a Au(111) support. Electrochemical scanning tunneling microscopy (EC‐STM) reveals that the electrochemical reduction occurs at much lower potentials than that for simple Pd salt solutions. The resulting particles are one atomic layer high and show a narrow size distribution. Precursor mass transport limitations and preconditioning of the solid‐liquid interface at low potentials influence the obtained morphology. In particular, a concomitant reduction mechanism via formation of molecular hydrogen is discussed. The deposited clusters show the typical behavior of small metallic Pd islands in EC‐STM: The apparent cluster height increases reversibly when lowering the potential close to the onset of hydrogen evolution, which is attributed to hydrogen adsorption. Abstract : Size‐control under investigation : A method to deposit small size‐controlled palladium clusters using a 12‐Pd II ‐oxo‐metalate precursor is presented. The resulting particle size depends on the electrochemical conditions at the solid‐liquid interface, revealing a second deposition pathway that is hydrogen‐induced. The resulting metallic Pd clusters show a reversible height increase in the electrochemical STM at the onset of hydrogen evolution.